Placing Advanced Placement® Human Geography: Its Role in U.S. Geography Education. Issue 3 (3rd May 2016) - Bednarz, Sarah Witham
ABSTRACT: This article examines Advanced Placement Human Geography (AP HG) in the context of its place in efforts to reform geography education. It presents a critical analysis of the AP program and its curriculum, asserting that it represents "powerful knowledge" as conceptualized by Young. It concludes with a call for research in AP HG aligned with recommendations to focus geography education research. Geographers in higher education are encouraged to embrace AP HG as a mechanism to recruit students and majors.